In Vitro Antioxidant and Antimicrobial Activities of Mondia whitei (Hook. f.) Skeels - Idayat Titilayo Gbadamosi ,; Sakiru Morenikeji Erinoso, (Journal of Basic & Applied Sciences, 2015)
Mondia whitei (Periplocaceae)is an aromatic plant used as aphrodisiac and for the treatment of urinary infection, jaundice, headache and diarrhoea in Nigeria. The plant was screened for phytochemical components using standard techniques. The antioxidant and antimicrobial activities of the plant were evaluated. The free radical scavenging activity was determined by 2, 2-diphenyl-1-picryl hydrazyl (DPPH) assay. The antimicrobial activity of M. whitei extracts against nine clinical isolates was determined by agar well diffusion method. Data were statistically analysed. The root was richer in saponins and tannins than the leaf whereas the leaf contained more flavonoids. The root gave 47.23% inhibition against DPPH+. There was positive correlation between the polyphenolic content and the antioxidant activity of the plant parts. At 300mg/ml, the water extracts of both the leaf and root were more active than the ethanolic extracts. The higher antimicrobial activity of the water extract could be attributed to the solubility of active constituents of the plant in water. The root showed higher antioxidant and antimicrobial activities than the leaf. M. whitei root could be very effective in the management of metabolic and infectious diseases. However, toxicological studies will confirm its safety in administration.